Formation of superhydrophobic surface with enhanced hardness and wear resistance by electrical discharge coating process. (May 2021) - Tyagi, Rashi; Das, Alok Kumar; Mandal, Amitava
Abstract: Electrical discharge coating (EDC) process is applied for preparation of hard and wear-resistant coating by using green compact tool of Cu+MoS2 +WS2 +hBN powder. XRD analysis suggests that the coating morphologies comprises of hard and soft phases. Further, EDS line scan along cross-section reveals that concentration of coating elements increases from workpiece to coating surface direction. FESEM results indicate that applied coatings exhibit a hierarchical rough structure. Due to the hierarchical coating structure, the water contact angle (WCA) is raised to a super-hydrophobic state (152.2°). The developed coatings also exhibit higher microhardness and low specific wear rates than substrate. It is aimed that the enhancement in mechanical durability of superhydrophobic surfaces will be beneficial for the extensive application of a superhydrophobic coating. Graphical abstract: Image 1 Highlights: Preparation of hard and lubricant coating using Cu + WS2 +MoS2 +hBN powders through EDC process. Production of superhydrophobic surfaces through EDC process. Examining the influence of hard and solid lubricant phases on the surface properties. Investigation on effect of EDC parameters on hydrophobicity of coated surface. Description on in-depth wear mechanism of coated layers.